EFECT OF CARBAMIDE PEROXIDE ON DENTAL ENAMEL TROUGH DIFERENT CONCENTRATIONS AND EXPOSURE TIMES - Pérez Vargas, Luis Femando (2004)
The purpose of this study was to evaluate variation of superficial morphology, histological structure and enamel color of vestibular side of anterior dental pieces exposed to different carbamide peroxide concentrations and exposure times. Our research was taken on 21 extracted teeth that where divided in three groups and subjected to different concentrations of carbamide peroxide gel which were : Group 1 with 5% concentration, group 2 with 10% concentration and group 3 with 20% concentration. The vestibular side of each tooth was divided into 4 sections, each of which ones was exposed to 5, 20 and 40 hours of whitening respectively, while the remaining section was the control group. The results were subjected to the Friedman test to establish statistical differences. It was concluded that morphologically, variations on the surface aspect were minimal with 5% concentration gel during 5, 20 and 40 hours of expositions. Groups 2 and 3 showed significant variation since the external surface became irregular Histologically, in group 1 there were no significant changes in prisms direction, but in groups 2 and 3 there were changes in prisms direction and microporosity increase.